Postoperative Outcomes of Transhiatal Esophagectomy in Patients with Esophageal Cancer, at Babol University Hospitals, from 2005 to 2015 - Y Asghari (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2017)
BACKGROUND AND OBJECTIVE: According to the importance of the esophageal cancer problem in northern provinces of Iran, and also high volume of transhiatal esophagectomy operations at Babol university hospitals, this study was conducted to identifying postoperative short term outcomes of transhiatal esophagectomy in patients with esophageal cancer. METHODS: This cross-sectional study was done on 114 patients with diagnosis of esophageal cancer that underwent transhiatal esophagectomy in Babol university hospitals, north of Iran, from 2005 to 2015. The study data were analyzed applying SPSS for windows (version 23), T-test, 2-independent sample chi-square and exact fisher test. FINDINGS: Of 114 patients, 62 of cases (54.4%) was male and 52 of them (45.6%) was female. The mean age of the patients was 62.25year. The most common symptom of the patients was dysphagia (99.1%). Pathologic feature of the tumors was squamous cell carcinoma in 89.5% of cases. The most common postoperative complications were arrhythmia (13.3%) and pleural effusion (10.5%). Mean admission duration was 9.31±2.94 days. Anastomosis site leak occurred in 8 patients (7.1%). In operation and in hospital mortality occurred for 1 cases (0.9%) and 4 cases (3.5%) respectively. CONCLUSION: On the basis of this study, Babol university hospitals has good result for postoperative outcomes of transhiatal esophagectomy comparing with other centers especially about admission time, need for tube thoracostomy, anastomosis site leak rate, and mortality rate.